Two NCA1 isoforms interact with catalase in a mutually exclusive manner to redundantly regulate its activity in rice - Liu, Jianzhe (BMC Plant Biol, 2019)
BACKGROUND: NCA1 (NO CATALASE ACTIVITY 1) was recently identified in Arabidopsis as a chaperone protein to regulate catalase (CAT) activity through maintaining the folding of CAT. The gene exists mainly in higher plants; some plants, such as Arabidopsis, contain only one NCA1 gene, whereas some others such as rice harbor two copies. It is not yet understood whether and how both isoforms have functioned to regulate CAT activity in those two-copy-containing plant species. RESULTS: In this study, we first noticed that the spatiotemporal expression patterns of NCA1a and NCA1b were very similar in rice plants. Subsequent BiFC and yeast three-hybrid experiments demonstrated that both NCA1a and NCA1b show mutually exclusive, rather than simultaneous, interaction with CAT. For a further functional analysis, nca1a and nca1b single mutants or double mutants of rice were generated by CRISPR/Cas9. Analysis on these mutants under both normal and salinity stress conditions found that, as compared with WT, either nca1a or nca1b single mutant showed no difference at phenotypes and CAT activities, whereas the double mutants constantly displayed very low CAT activity (about 5%) and serious lesion phenotypes. CONCLUSIONS: These results suggest that NCA1a and NCA1b show mutually exclusive interaction with CAT to regulate CAT activity in a functionally-redundant manner in rice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-019-1707-0) contains supplementary material, which is available to authorized users.